Upaya Meningkatkan Kemampuan Bahasa Ekspresif Melalui Permainan Tradisional Oray - Orayan pada Anak Usia Dini 5-6 Tahun di Taman Kanak-Kanak Istiqomah - Aprilia, Lala; Elnawati, Elnawati; Maulana, Redi Awal (Bageur: Jurnal Ekonomi, Sosial, dan Pendidikan, 2026)
Expressive language skills are one of the important aspects in early childhood language development, because they relate to children's ability to express thoughts, feelings, and ideas orally. However, the results of initial observations at Istiqomah Kindergarten show that the expressive language skills of children aged 5-6 years are still relatively low. This can be seen from children who are less able to express their opinions, the limited vocabulary used, and the lack of courage to speak in front of peers. This research aims to improve early childhood expressive language skills through traditional snake games. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles, with each cycle including the stages of planning, implementation, observation, and reflection. The subjects of the study were children aged 5–6 years at Istiqomah Kindergarten. Data collection techniques are carried out through observation, documentation, and field notes. Data analysis was carried out descriptively, qualitatively, and quantitatively. The results of the study show that the application of traditional snake games can improve children's expressive language skills. The improvement can be seen in the child's ability to express opinions, answer questions, communicate verbally, and have the courage to speak during learning activities. Thus, it can be concluded that the traditional game of snakes is effectively used as one of the learning strategies to improve early childhood expressive language skills.